The Influence Of Product Quality And Price Perception On Customer Satisfaction (Survey Of Azqia Collection Tasikmalaya Customers) - Ulfah Fitriyyah; Depy Muhamad Pauzy; Suci Putri Lestari (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the influence of product quality and price perception on customer satisfaction (Survey on customers of Azqia Collection Tasikmalaya). The method used in this study is causality through a survey approach. With a research sample of 100 customers of Azqia Collection Tasikmalaya. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that product quality and price perception had a significant effect on customer satisfaction at Azqia Collection Tasikmalaya). Partially, product quality has a significant influence on customer satisfaction at Azqia Collection Tasikmalaya). Partially Price Perception has a significant influence on Customer Satisfaction at Azqia Collection Tasikmalaya).